Right Ventricular Outflow Tract Tachycardia with Structural Abnormalities of the Right Ventricle and Left Ventricular Diverticulum - Bortolo Martini; Nicola Trevisi; Nicolò Martini; Li Zhang (Case Reports in Cardiology)
A 43-year-old woman presented to the emergency room with a sustained ventricular tachycardia (VT). ECG showed a QRS in left bundle branch block morphology with inferior axis. Echocardiography, ventricular angiography, and cardiac magnetic resonance imaging (CMRI) revealed a normal right ventricle and a left ventricular diverticulum. Electrophysiology studies with epicardial voltage mapping identified a large fibrotic area in the inferolateral layer of the right ventricular wall and a small area of fibrotic tissue at the anterior right ventricular outflow tract. VT ablation was successfully performed with combined epicardial and endocardial approaches.